West Pacific climate and circulation over the last 160 kyr: A palaeontological and geochemical multiproxy reconstruction within the inflow path of the Indonesian Throughflow - Bolliet, Timothé Geoffroy (Universitat Kiel, 2010)
Understanding the Earth´s present day climate and predicting its future evolution require investigation of high resolution sedimentary archives providing critical information of past oceanic and atmospheric variability. This study is based on two continuous marine sedimentary successions (Cores MD06-3067 and MD06-3075), recovered close to Mindanao Island (Philippines). The Indo-Pacific region represents a major source of heat and moisture, which are redistributed to the high latitudes by atmospheric and oceanic circulations; thus this region is a major actor in regulating global climate. The two cores investigated in this work are located within the inflow path of the Indonesian Throughflow. This ocean current provides a critical link within the thermohaline circulation by transferring relatively cold and fresh upper water from the equatorial western Pacific to the Indian Ocean through the complex seaways of the Indonesian archipelago, in turn affecting atmospheric and oceanic circulation within the entire Pacific and Indian Oceans. Our data indicate that Core MD06-3067 (1575 m water depth) provides an essential archive of atmospheric and surface to mid-depth oceanic circulation for the western equatorial Pacific over the last 160 kyr. Paleotemperature reconstruction performed on surface and deep-dwelling species of foraminifera from this core indicates largeamplitude variations in sea surface and thermocline temperatures and major fluctuations of the upper ocean thermal contrast occurring on glacial-interglacial and suborbital timescales. These variations in upper-ocean thermal contrast are interpreted as reflecting changes in the activity of a major regional upwelling system (Mindanao Dome). Enhanced activity of the Mindanao Dome during the last glacial maximum and MIS 4 compared to MIS 6 is revealed by anomalously cold surface waters and increased productivity, indicated by coccolith and benthic foraminiferal assemblages. In contrast, high sea surface temperature resulting from episodic decreases in the activity of the dome coincide with Antarctic warm events A1-4. These fluctuations in upwelling activity appear related to latitudinal migrations of the Intertropical Convergence Zone, inducing fundamental changes in monsoonal wind regimes and oceanic circulation patterns. Oxygen and carbon stable isotopes analysis performed on benthic foraminifera from Core MD06-3067 in the open west Pacific Ocean indicate long-term influence of mid2 depth water originating from the Southern Ocean, interrupted during terminations I and II by abrupt incursions of 13C-depleted water masses coming from the North Pacific. These sudden shifts in the intermediate and deep water circulations close to Mindanao island indicate major re-organization of the latitudinal extent of the middepth water masses in the whole Pacific basin, related to glacial/interglacial climatic transitions. Comparison with stable isotope records from the deeper Core MD06-3075 (1878 m), located in the more marginal Davao Gulf, indicates a highly contrasted evolution of the mid-depth circulation at these two sites over the last termination. Lower benthic δ13C values in Core MD06-3075, particularly during MIS2, reflect poorer ventilation and/or differences in carbon export flux at this more proximal location within the Davao Gulf. There is no evident incursion of North Pacific intermediate or deep water during deglaciation, possibly due to the relative isolation of the Davao Gulf from the open Pacific Ocean and/or to different sourcing of deep and intermediate waters at this site. Für das Verständnis des heutigen globalen Klimas und für Vorhersagen der zukünftigen Klimaentwicklung ist die Erforschung hochauflösender sedimentärer Archive früherer mariner und atmosphärischer Klimavariablität eine unabdingbare Voraussetzung. Die hier vorgelegte Arbeit beruht auf zwei kontinuierlichen marinen Sedimentabfolgen (MD06-3067 und MD06-3075), die in der Nähe von Mindanao (Philippinen) gekernt wurden. Die Indo-Pazifische Region stellt heute eine bedeutende Quelle von Wärme und Feuchtigkeit dar, die von dort durch atmosphärische und marine Zirkulation in hohe Breiten transportiert werden; dadurch wird diese Region zu einem bedeutenden Faktor für das globale Klimagleichgewicht. Die beiden untersuchten Kerne liegen im Einstrombereich des indonesischen Durchstroms. Dieser Ozeanstrom transportiert heute relativ kühle und süsse oberflächennahe Wassermassen in einer komplexen Passage durch den indonesischen Archipel vom äquatorialen Westpazifik in den indischen Ozean und stellt damit nicht nur ein kritisches Bindeglied in der globalen thermohalinen Zirkulation dar, sondern beeinflußt damit auch die atmosphärischen und ozeanischen Strömungsmuster sowohl im Pazifik als auch im indischen Ozean. Kern MD06-3067 aus 1575 m Wassertiefe stellt ein ausgezeichnetes Archiv der Zirkulation in der Atmosphäre und der oberflächennahen- bis intermediären Wassermassen im westlichen äquatorialen Pazifik während der letzten 160 000 Jahre dar. Paläotemperatur-Rekonstruktionen an oberflächennah und in größeren Wassertiefen um 100 m lebenden planktonischen Foraminiferen zeigen bedeutende Schwankungen der Meeresoberflächen- und Thermoklinen-Temperaturen auf glazialen-interglazialen und suborbitalen Zeitskalen. Diese Variabilität in den Temperaturen des oberen Ozeans wird als Ausdruck der Aktivität des bedeutenden 6 wird durch ungewöhnlich kalte Oberflächenwassermassen und erhöhte Produktivität (Coccolithen und benthische Foraminiferengemeinschaften) angezeigt. Hohe Oberflächentemperaturen, die mit einer Abschwächung der Aktivität des Mindanao Dome in Zusammenhang stehen, entsprechen den Antarktischen Warm-Ereignissen 6 A1-4. Diese Schwankungen der Auftriebsaktivität werden mit meridionalen Verschiebungen der intertropischen Konvergenzzone in Zusammenhang gebracht, die grundlegende Änderungen des lokalen Monsun-Windregimes und der daraus resultierenden ozeanischen Zirkulationsmuster nach sich ziehen. Sauerstoff und Kohlenstoffisotopenanalysen an benthischen Foraminiferen des Kerns MD06-3067 im offenen West Pazifik zeigen den langfristigen Einfluß intermediärer Wassermassen aus dem Südozean, der nur kurzfristig während der Glazialen Terminationen I und II durch abruptes Einströmen 13C-armer Wassermassen aus dem Nord-Pazifik unterbrochen wurde. Diese plötzlichen Änderungen der intermediären und Teiefenwasserzirkulation vor Mindanao belegen bedeutende Fluktuationen der meridionalen Ausdehnung intermediärer Wassermassen im Pazifik während glazialerinterglazialer Klimawechsel. Ein Vergleich mit benthischen stabilen Isotopensignalen des tieferen Kerns MD06-3075 (1878 m), der innerhalb des Davao Golfs gelegen ist, zeigt deutliche Unterschiede in der Entwicklung der intermediären Zirkulation zwischen diesen beiden Lokationen. Niedrigere δ13C-Werte in Kern MD06-3075, speziell während MIS2, spiegeln eine geringere Ventilation und/oder höheren Kohlenstofffluß an dieser proximaleren Lokalität im Davao Golf wieder. Es gibt hier keine Hinweise auf den Einfluß von nordpazifischem Zwischenwasser während der glazialen Termination, was wahrscheinlich an einer Barriere zum offenen Pazifik und damit an einer unterschiedlicher Herkunft der tiefen und intermediären Wassermassen an dieser Lokalität liegt.